Exploring Pragmatic Markers in The Reluctant Fundamentalist: A Corpus-Based Analysis of Mohsin Hamid's Narrative Techniques - Sidra-Tul-Muntaha; Ammara Noreen; Rafia Bilal (Corporum)
In the present research, pragmatic markers are examined in the context of Mohsin Hamid's novel, The Reluctant Fundamentalist, focusing on the narrative sequence and character identity construction. The linguistic and cultural roles of pragmatic markers, such as hedges and discourse markers, in the text are studied. Using a qualitative method supported by a corpus, the study classifies markers according to Fraser's typology. It places their use in the context of Bhabha's notion of the "third space" and hybridity. The corpus analysis shows that words like "and," "however," and "think" enhance the story by expressing the protagonist's emotional problems, cultural hybridity, and diasporic identity. Hedges stress reflection and ambiguity, whereas discourse markers offer coherence and indicate changes. This study shows that pragmatic markers are language tools that promote cohesiveness and serve as a vehicle for expressing cultural and emotional dimensions, offering insights into the complexities of diasporic literature. Furthermore, the findings advance corpus linguistics by showing how systematic corpus-based research may uncover trends in diasporic literature.